Simulated Pediatric Physician-Parent Email Cases - Jocelyn Schiller; Jennifer Christner; Patricia Keefer; Francis McBee-Orzulak; Terry Murphy; Kerry Mychaliska; Ken Pituch; Robert Stansfield; Kavita Warrier (Association of American Medical Colleges, 2012)
Abstract Physicians' use of electronic mail (email) communication with patients is increasing. A survey of American Academy of Pediatrics (AAP) members in 2001 reported only 14% used email with patients, but more recent studies suggest up to 71-74% of physicians use email with their patients. This matches the desire of parents of pediatric patients to use email communication with their physicians. In recent studies, 74% of parents expressed interest in using email to contact their child's physician and 80-84% felt that physicians should use email to communicate with patients. Numerous studies have confirmed the importance of clear patient-physician communication in health care outcomes. In response, several tools to teach and subsequently assess physicians' verbal communication and interpersonal skills have been developed but these, as well as most research on patient-physician communication, examine face-to-face communication skills. Accreditation bodies for both undergraduate and graduate medical education are clear that communication skills must be taught and assessed. We have found little evidence of email communication skills being taught across the continuum of learning. Because of this increased interest in email communication, our third year pediatric clerkship developed a curriculum on principles of email communication with patients. In our simulated emails, parents expressed concern, anger or confusion about their child's medical care. The four cases are: Parent refusing a Hepatitis B vaccination in newborn. Concern regarding a delay in treatment when a strep culture turned positive after negative rapid strep test results. Concern about radiation exposure from voiding cystourethrogram (VCUG) after 2nd urinary tract infection. Parent expecting antibiotics for otitis media. These simulated parent e-mails are used as a tool to aid in educating students about patient-physician communication and in evaluating students' medical knowledge, communication skills and professionalism. The cases and grading rubric were developed by a panel of medical educators. Inter-rater reliability between faculty members and student improvement between the first and final email assignment were previously described. Intraclass correlations of all ratings of each student response were used to estimate interrater reliability of total score (0.85), knowledge subscore (0.89), professionalism subscore (0.79), and the communication subscore (0.66). Although the students' first email response is not graded, for purposes of this study, the first email response was graded by faculty using the grading rubric. Students' performance on the first email case did not improve as the academic year progressed suggesting that this is not a skill that is learned as one acquires more clinical experience. The linear effect of date on total score on the first response was near zero (baseline performance improved less than 0.002 score points per month) and nonsignificant. Scores on the total and all subscales improved significantly from the first to the final testing. Students' total scores improved an average 2.42 points from mean=14.36 to mean=16.78 (P<.0001). Knowledge scores improved an average 1.49 points from mean=5.75 to mean=7.24 (P< .0001). Communication scores improved an average 0.42 points from mean=5.23 to mean=5.65 (P<.0001). Professionalism scores improved an average 0.51 points, from mean=3.38 to mean=3.89 (P<.0001).